VD_FINDINFO HC / 2014 / 1006 vom 1. Dezember 2014 - VD Tribunal cantonal (2014)
DIVORCE, DROIT DE GARDE, ENFANT, INTÉRÊT DE L'ENFANT, BIENS DE L'ENFANT, AUTORITÉ PARENTALE | 308 al. 1 CC, 308 al. 2 CC, 310 al. 1 CC